2020
DOI: 10.1162/qss_a_00072
|View full text |Cite
|
Sign up to set email alerts
|

All downhill from the PhD? The typical impact trajectory of U.S. academic careers

Abstract: Within academia, mature researchers tend to be more senior, but do they also tend to write higher impact articles? This article assesses long-term publishing (16+ years) United States (US) researchers, contrasting them with shorter-term publishing researchers (1, 6 or 10 years). A long-term US researcher is operationalised as having a first Scopus-indexed journal article in exactly 2001 and one in 2016-2019, with US main affiliations in their first and last articles. Researchers publishing in large teams (11+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In Australia, researchers (from three sampled universities) with academic ages 10-29 attract the most citations per publication (Gu & Blackmore, 2017). In the USA (using many of the same methods as the current study, but focusing on long-term researchers authoring at least 5 papers), average citations per publication do not tend to increase over careers, and may tail off towards the end of careers or start to decrease after about a decade (Thelwall, & Fairclough, 2020). For a set of Spanish research council members, younger researchers tended to have higher productivity and citation impact indicators (Costas, van Leeuwen, & Bordons, 2010), but a study of Mexican researchers found almost the opposite (González-Brambila, & Veloso, 2007), either through different methods or international differences.…”
Section: Academic or Physical Age And Citation Impactmentioning
confidence: 71%
See 3 more Smart Citations
“…In Australia, researchers (from three sampled universities) with academic ages 10-29 attract the most citations per publication (Gu & Blackmore, 2017). In the USA (using many of the same methods as the current study, but focusing on long-term researchers authoring at least 5 papers), average citations per publication do not tend to increase over careers, and may tail off towards the end of careers or start to decrease after about a decade (Thelwall, & Fairclough, 2020). For a set of Spanish research council members, younger researchers tended to have higher productivity and citation impact indicators (Costas, van Leeuwen, & Bordons, 2010), but a study of Mexican researchers found almost the opposite (González-Brambila, & Veloso, 2007), either through different methods or international differences.…”
Section: Academic or Physical Age And Citation Impactmentioning
confidence: 71%
“…Whilst the average numbers of co-authors varies substantially between countries and fields (Thelwall & Maflahi, 2020), the purpose of the threshold is to eliminate the possibility that the results are affected by highly collaborative authors that may have contributed little to their publications. The threshold ten was used in the similar prior study of the USA (Thelwall & Fairclough, 2020), and accounts for less than 3% of articles in all broad fields (Thelwall & Maflahi, 2020). The results will therefore not be relevant for research fields that routinely collaborate more, such as in high value large international health-related studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, perhaps senior researchers mainly used questionnaires in 1996, needing funding to deliver and administer them, whereas PhD students nowadays are more common users, with the technological skills to use them easily. Seniority does not necessarily associate with increased citation impact (in the USA: Thelwall & Fairclough, 2020a), so seniority alone may not be the reason, but it seems possible that more expensive research methods would be applied more carefully, other factors being equal. For example, web‐based surveys seem to be reported less carefully than offline surveys (Turk et al, 2018).…”
Section: Discussionmentioning
confidence: 99%